2016
DOI: 10.1042/cs20160047
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in chronic kidney disease: progression to end-stage renal disease and haemodialysis

Abstract: Sex and gender differences are of fundamental importance in most diseases, including chronic kidney disease (CKD). Men and women with CKD differ with regard to the underlying pathophysiology of the disease and its complications, present different symptoms and signs, respond differently to therapy and tolerate/cope with the disease differently. Yet an approach using gender in the prevention and treatment of CKD, implementation of clinical practice guidelines and in research has been largely neglected. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
156
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(177 citation statements)
references
References 214 publications
7
156
0
14
Order By: Relevance
“…The effect of gender on CKD progression remains a topic of debate; the majority of evidence points toward better outcomes in female patients [20,21]. This has been further confirmed in a recent meta-analysis, where male sex and substantial proteinuria were found to be significant perpetuating factors for the progression from latestage CKD to ESRD [22].…”
Section: Discussionmentioning
confidence: 53%
“…The effect of gender on CKD progression remains a topic of debate; the majority of evidence points toward better outcomes in female patients [20,21]. This has been further confirmed in a recent meta-analysis, where male sex and substantial proteinuria were found to be significant perpetuating factors for the progression from latestage CKD to ESRD [22].…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have demonstrated sex differences in renal damage among healthy and diabetic individuals [16]. In non-diabetic individuals with chronic kidney disease, male sex has been identified as a risk factor for rapid decline in renal function as opposed to pre-menopausal women [17]. In diabetic individuals conflicting reports exist in different populations; a recent study among Japanese subjects with type 2 diabetes identified a higher risk in women [18], whereas a report regarding European individuals indicated an increased risk for renal decline in men [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sex has an impact on the development and progression of vascular and renal disease [1214]. A number of experimental studies in Apoe -deficient mice detected sex differences in the development and progression of vascular and renal disease [15].…”
Section: Introductionmentioning
confidence: 99%